World economy still ailing - Günter Großer (Intereconomics, 1983)
1982 was yet another year of international economic disappointment. The frequently forecast gradual recovery of demand and production during the course of the second half of the year did not materialise. In fact, Western Europe once again experienced another pronounced downturn. However, at least in the majority of leading industrialised countries, the conditions for growth have definitely improved. Will 1983 bear witness to the turning of the recessionary tide?
Keywords: 330; Economic Trends